2015
DOI: 10.5489/cuaj.2732
|View full text |Cite
|
Sign up to set email alerts
|

Experience with sliding-clip splenorrhaphy for splenic injury during radical nephrectomy

Abstract: Introduction: We report our experience with sliding-clip splenorrhaphy (SCS), a novel splenic conservation technique, for iatrogenic splenic injury (ISI) during a left radical nephrectomy (RN). We also reviewed the literature on ISI. Methods: We retrospectively reviewed data from patients who had RN between January 2005 and December 2013 at our institution. The technique used was similar to sliding-clip renorrhaphy. Our Medline literature identified articles containing "splenic injury during nephrectomy," "iat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In 1996, Cooper et al reported that 4.3% of left nephrectomies resulted in splenectomy [ 74 ]. In more recent papers, the rate was between 4.2% and 5.13% [ 7 , 75 ]. In the case of thoracoscopic spinal surgery, the spleen can be vulnerable to iatrogenic injury due to its proximity to the thoracolumbar junction [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, Cooper et al reported that 4.3% of left nephrectomies resulted in splenectomy [ 74 ]. In more recent papers, the rate was between 4.2% and 5.13% [ 7 , 75 ]. In the case of thoracoscopic spinal surgery, the spleen can be vulnerable to iatrogenic injury due to its proximity to the thoracolumbar junction [ 6 ].…”
Section: Discussionmentioning
confidence: 99%